Preconditioning of the tumor microenvironment with oncolytic reovirus converts CD3-bispecific antibody treatment into effective immunotherapy. Issue 2 (20th October 2020) - Groeneveldt, Christianne; Kinderman, Priscilla; van den Wollenberg, Diana J M; van den Oever, Ruben L; Middelburg, Jim; Mustafa, Dana A M; Hoeben, Rob C; van der Burg, Sjoerd H; van Hall, Thorbald; van Montfoort, Nadine
Abstract : Background: T-cell-engaging CD3-bispecific antibodies (CD3-bsAbs) are promising modalities for cancer immunotherapy. Although this therapy has reached clinical practice for hematological malignancies, the absence of sufficient infiltrating T cells is a major barrier for efficacy in solid tumors. In this study, we exploited oncolytic reovirus as a strategy to enhance the efficacy of CD3-bsAbs in immune-silent solid tumors. Methods: The mutant p53 and K-ras induced murine pancreatic cancer model KPC3 resembles human pancreatic ductal adenocarcinomas with a desmoplastic tumor microenvironment, low T-cell density and resistance to immunotherapy. Immune-competent KPC3 tumor-bearing mice were intratumorally injected with reovirus type 3 Dearing strain and the reovirus-induced changes in the tumor microenvironment and spleen were analyzed over time by NanoString analysis, quantitative RT-PCR and multicolor flow cytometry. The efficacy of reovirus in combination with systemically injected CD3-bsAbs was evaluated in immune-competent mice with established KPC3 or B16.F10 tumors, and in the close-to-patient human epidermal growth factor receptor 2 (HER2) + breast cancer model BT474 engrafted in immunocompromised mice with human T cells as effector cells. Results: Replication-competent reovirus induced an early interferon signature, followed by a strong influx of natural killer cells and CD8 + T cells, at the cost of FoxP3 + Tregs. Viral replication declined after 7 days and was associated with a systemic activation of lymphocytes and the emergence of intratumoral reovirus-specific CD8 + T cells. Although tumor-infiltrating T cells were mostly reovirus-specific and not tumor-specific, they served as non-exhausted effector cells for the subsequently systemically administered CD3-bsAbs. Combination treatment of reovirus and CD3-bsAbs led to the regression of large, established KPC3, B16.F10 and BT474 tumors. Reovirus as a preconditioning regimen performed significantly better than simultaneous or early administration of CD3-bsAbs. This combination treatment induced regressions of distant lesions that were not injected with reovirus, and systemic administration of both reovirus and CD3-bsAbs also led to tumor control. This suggests that this therapy might also be effective for metastatic disease. Conclusions: Oncolytic reovirus administration represents an effective strategy to induce a local interferon response and strong T-cell influx, thereby sensitizing the tumor microenvironment for subsequent CD3-bsAb therapy. This combination therapy warrants further investigation in patients with non-inflamed solid tumors.